Simbolisme Motif Batik Pada Budaya Tradisional Jawa dalam Perspektif Politik dan Religi - V. Kristanti Putri Laksmi (Ornamen, 2010)
Batik art is one of the everlasting and an extra ordinary lagacy  from the Indonesian culture and it has a very deep meaning or sense. There are so many thing that can be revealed through the batik art, such as the background of the culture, faith, customs and tradition, characteristic and manners, savor, skill, etc.  It can be found in the form of various ornaments on the batik  itself. Every sheet of batik cloth reflects a massage and hope about a better future for the person who wears it. The massage is clearly visible through the form of the various ornaments that painted on the batik cloth.  On classical batik, every motif and design ornaments have a  relation with the function of the clothes itself It is caused by every kinds of batik and the distinctive various of ornaments have their own spiritual meaning that can be related with the person who wears it and the event.  On the other hand, the form of the various batik ornaments  have an implicit meaning in the form of religion perspective or political perspective.  Key words: the form of various ornaments on the batik, the meaning